Attitude in Learning as a Mediator for Engagement and Academic Performance in Mathematics - Carcueva, Raymund (Journal of Interdisciplinary Perspectives, 2025)
This study specifically focuses on mathematics, as it plays a crucial role in educational settings and is a fundamental subject for academic success. By examining the mediating effect of attitude on learning and its relationship with engagement, the research aims to understand how these variables contribute to academic performance in mathematics. The researcher used adapted survey questionnaires to collect information from 148 randomly selected respondents using the "Fishbowl Draw Method." Descriptive statistics, the Pearson product-moment correlation coefficient, and regression analysis were employed as statistical tools to analyze the data. These analyses indicated that students exhibited a high level of engagement, academic performance, and attitude toward learning mathematics. A significant relationship was found between student engagement and academic performance in mathematics, as well as between student engagement and attitude toward learning. However, the relationship between attitude toward learning and academic performance was not significant. Moreover, the impact of student engagement on academic performance was observed solely through its direct influence and not via an indirect effect stemming from attitudes toward learning. Accordingly, considering that attitude toward learning does not mediate the relationship between engagement and academic performance, students should focus on strengthening their classroom engagement to improve their academic performance. Future researchers are recommended to investigate other variables such as teaching methods and students' learning styles as mediators.